2013
DOI: 10.3109/09593985.2013.845806
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical evaluation of elastic tubes used in physical therapy

Abstract: Mechanical tests revealed different elastic forces for different levels of elongation of each tube. The replication of the results in clinical situations is recommended, so the elastic resistance in clinical routine could be evaluated with more propriety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
0
17
0
2
Order By: Relevance
“…The dynamic determination on ER, just like on the present study, has been performed from the initial-length samples (< 100 mm) shorter than those used in practice (Azevedo et al, 2003;Patterson et al, 2001;Santos et al, 2009;Simoneau et al, 2001). Nevertheless, force versus deformation relationships have been commonly applied instead of the original length (%), which is based on the assumption that the elastic material properties are constant (Patterson et al, 2001;Santos et al, 2009;Simoneau et al, 2001;Thomas et al, 2005). In support of this argument, Patterson et al (2001) and Thomas et al (2005) showed that different lengths could produce similar-force responses with the same relative deformation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The dynamic determination on ER, just like on the present study, has been performed from the initial-length samples (< 100 mm) shorter than those used in practice (Azevedo et al, 2003;Patterson et al, 2001;Santos et al, 2009;Simoneau et al, 2001). Nevertheless, force versus deformation relationships have been commonly applied instead of the original length (%), which is based on the assumption that the elastic material properties are constant (Patterson et al, 2001;Santos et al, 2009;Simoneau et al, 2001;Thomas et al, 2005). In support of this argument, Patterson et al (2001) and Thomas et al (2005) showed that different lengths could produce similar-force responses with the same relative deformation.…”
Section: Discussionmentioning
confidence: 99%
“…ER has been mainly quantified by static calibration tests, where the stress-strain relationship is obtained by recording the force response (weights or force transducers) associated with its displacement (deformation) from the initial length (Anderson et al, 2008;Cronin et al, 2003;Mcmaster et al, 2010;Rhea et al, 2009;Shoepe, Ramirez, & Almstedt, 2010;Thomas, Mueller, & Busse, 2005;Wallace et al, 2006). Despite the fact that the tested materials have viscoelastic properties, there is no agreement on the type of adjustment of regression models (linear, quadratic or logarithmic) provided to users (Anderson et al, 2008;Cronin et al, 2003;Mcmaster et al, 2010;Santos et al, 2009;Shoepe et al, 2010;Thomas et al, 2005). Additionally, although dynamic calibration testing demonstrates a non-linear distortion behavior, no regression models for natural rubber devices (NRET) (Patterson et al, 2001;Santos et al, 2009;Simoneau et al, 2001) and alternative synthetic rubbers have been reported (LET) (Azevedo, Benatti, Alves, & Filho, 2003).…”
Section: Palavras Chavementioning
confidence: 99%
See 3 more Smart Citations